Análisis del control interno de la gestión financiera del GAD Parroquial de Febres Cordero - Díaz Berruz, Faridde Francisca (2020)
At present, public entities are framed by different factors that can cause problems within them. Due to this, the following case study is presented entitled "ANALYSIS OF INTERNAL CONTROL OF THE FINANCIAL MANAGEMENT OF THE PARISH GAD OF FEBRES CORDERO" whose objective is to identify the problems that exist on internal control and financial management, it should be emphasized that the Rural Parish Autonomous Governments are legal entities of public law with political, administrative and financial autonomy that are regulated by a maximum authority, in order to fully carry out the projects or works to be executed for the good living of the citizens represented, therefore, an excellent internal control must be carried out over each of the activities carried out in the Parish Gad since internal control deals with the management process that is maintained to be administered, which are variables that are closely related to financial management in order to meet the proposed and proposed objectives, it is worth mentioning that the problems found in the Febres Cordero Parish Gad are also due to the economic situation facing the Country due to the budget reduction, lowering the monthly budget of the Febres Cordero Parish Gad and these resulting in the cancellation of projects and works, the reduction of salaries to officials etc., in addition, all entities, whether public or private, must carry out the respective financial analyzes, as this makes it possible to determine the variations in the financial plans in order to comply with the projects.